STRATEGI PENGEMBANGAN PARIWISATA PANTAI PARAGTRITIS - Rahmawati, Nova Ida; Sayekti, lulu Anastesi (PARADIGMA: Jurnal Ilmu Administrasi, 2025)
The diversity of tourism potential is one of the factors that contribute to regional and national income. Parangtritis Beach is one of the tourist attractions that offers various potentials. However, this destination still faces several challenges, including a declining trend in visitors from 2022 to 2024, waste management issues, visitor complaints about poorly maintained facilities and unorganized vendors, inadequate beach safety with several dangerous rip current zones, and underutilized accommodations. The purpose of this study is to identify the strengths, weaknesses, opportunities, threats, and development strategies of Parangtritis Beach tourism through SWOT analysis. This research applied a qualitative descriptive method. Data analysis was conducted using the Miles and Huberman model. The research indicators covered internal factors (attraction, accessibility, amenities, ancillary) and external factors (government policy, institutions, competition, technology, and customers). The findings formulated development strategies for Parangtritis Beach: Maintaining natural attractions, developing tour packages, strengthening digital promotion, organizing thematic events, and creating dedicated media accounts; Involve community empowerment, local training, construction of art stages, integration of accommodation information, and reactivation of the tourism information center; hosting unique events, distinctive branding, diversifying facilities, and private sector collaboration; securing funding for facility improvements, optimizing accommodation supervision, and waste management through waste banks, education, and strict sanctions. In conclusion, Parangtritis Beach holds significant potential but continues to face challenges, making strategic development essential. Recommendations include integrated beach environmental management, revitalization of tourism information services and digital promotion, improvement of facilities with accommodation regulation, development of tour packages, and strengthening cross-stakeholder collaboration.